Analisis Pengaruh Locus of Control dan Financial Literacy Terhadap Minat Investasi di Lembaga Keuangan Syariah - Anjellah, Rati; Umah, Khurul Aimmatul (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2024)
This quantitative descriptive research aims to find out how locus of control and financial literacy influence investment interest in Islamic financial institutions, both partially and simultaneously. Data was taken using a Likert-scale questionnaire from 100 respondents selected using purposive sampling. Data analysis was carried out using descriptive analysis and multiple regression statistical analysis using analytical tools, namely IBM SPSS 22. The results of the research show that locus of control partially does not influence does not influence investment interest in sharia financial institutions. Meanwhile, financial literacy partially has a positive and significant influence on investment interest in sharia financial institutions. Simultaneously, locus of control and financial literacy have a positive and significant influence on investment interest in sharia financial institutions.